The ANALISIS KINERJA STRUKTUR GEDUNG KULIAH TERPADU PPNS MENGGUNAKAN METODE SISTEM GANDA: Indonesia - Mochamad Ilham Zulfar; Sumaidi; Wahyu Kartini (Racic : Rab Construction Research, 2025)
The Integrated Lecture Building of the State Polytechnic of Shipbuilding Surabaya is constructed vertically or in multiple stories. However, multi-story buildings are vulnerable to lateral loads such as earthquakes and strong winds, especially since Surabaya has the potential for seismic activity. Therefore, the building must be designed to possess optimal structural resistance to lateral loads, such as earthquakes. In this study, the building is designed using a dual system, which is a combination of moment-resisting frames and shear walls to enhance the even distribution of lateral loads. The performance evaluation method used in the building design is a nonlinear static method, namely pushover analysis, based on ATC-40 guidelines. Based on the analysis results, the structural performance level falls under the Immediate Occupancy (IO) classification and exhibits full ductility.